Cancer Stem Cells and Neuroblastoma: Characteristics and Therapeutic Targeting Options - Veschi, Veronica; Verona, Francesco; Thiele, Carol J. (Frontiers in Endocrinology, 2019)
The majority of embryonal tumors or childhood blastomas derive from pluripotent progenitors or fetal stem cells which acquire cancer stem cell (CSC) properties: multipotency, self-renewal ability, metastatic potential, chemoresistance, more pronounced levels of drug transporters, enhanced DNA-damage repair mechanisms and a quiescent state. Neuroblastoma (NB) is considered a neuroendocrine tumor and the most common extracranial neoplasm in children. NB pathogenesis has been frequently associated with epigenetic dysregulation and a failure to implement a differentiation program. The origin, characteristics and isolation of the CSC subpopulation in NB are still incompletely understood, despite the evidence that this cell subset contributes to disease recurrence and acquired resistance to standard therapies. Here we summarize the literature regarding the isolation and characterization of CSCs in NB over the past decades from the early recognition that expression of stem cell factor (SCF) or its receptor c-KIT to more recent studies identifying the ability of G-CSF and STAT3 to support stem cell like properties in NB cells. Additionally we’ll review the morphologic variants of NB tumors whose recent epigenetic analyses has shed light on the tumor heterogeneity so common in NB. Mesenchymal stem cells NB-derived have been recently isolated from primary tumors of NB patients and associated with a pro-tumorigenic role in tumor microenvironment enabling tumor immune escape and contributing to their invasive and metastatic capabilities. In particular, we will focus on the epigenetic reprogramming in the CSC subpopulation in NB and strategies to target CSCs in NB.